Economic Viability and Marketing Networks of Finger Millet in North Coastal Andhra Pradesh - Beera, Anusha; Akkamahadevi Naik,; Ashok Kumar,; Idemakanti Chandrakanth Reddy, (Indian Journal of Extension Education, 2024)
Finger millet (Eleusine coracana) is vital in global agriculture for its nutritional value, adaptability, & capacity to tackle food security challenges. Data was gathered during 2024 from farmers, local traders, wholesalers and retailers in three districts of the North coastal region of Andhra Pradesh, i.e., Srikakulam, Vizianagaram, & Visakhapatnam, to know the major marketing channels of finger millet. This study analyzes the cost structure and marketing margins in finger millet production across three channels, detailing each stage from farmers (net price Rs. 3300-3320 per quintal) to retailers. Channel 1 had a final retail price of Rs. 5000 with a margin of Rs. 1681, Channel 2 reached Rs. 5500 with a margin of Rs. 2000, and Channel 3 peak at Rs. 6500 with a margin of Rs. 3170. Additionally, it details the costs per acre, with a gross return of Rs. 37950 and a net return of Rs. 1471, revealing a return per rupee of 1.04. The findings highlight the impact of each marketing stage on consumer prices.